Specific human capital intensity in Turkish manufacturing firms: The role of foreign ownership - ERİŞ DERELİ, BİLGE (My University, 2022)
Foreign direct investment (FDI) and human capital are considered as essential factors of both firms’ and countries’ growth. This property made them to be a major focus of policy in many nations. There is a large literature on the relationship between FDI (foreign direct investment) and growth, as well as the relationship between human capital and growth. However, despite its great empirical and policy relevance, the specific link between foreign ownership and human capital is a rather under-researched empirical subject. The main aim of this study is to analyze the relationship between foreign ownership and specific human capital in Turkish manufacturing sector. A micro level analysis is carried out using firm-level data retrieved at World Bank’s Turkey Enterprise Survey for the year 2019. Using fractional response regression methodology, several models are estimated to see if foreign ownership has an impact on firm human capital intensity, as well as other firm characteristics, industries, and regions. The key findings can be summarized as follows: i) private foreign ownership has a negative effect on firm-level specific human capital intensity; ii) being a larger or older firm negatively affects firms’ specific human capital intensity; iii) export intensity is the only firm characteristic that has a positive effect of specific human capital intensity.

Doğrudan yabancı yatırımlar ve beşeri sermaye hem ülkelerin hem de firmaların büyümesinde önemli bir faktör olarak değerlendirildiği için birçok ülkede politikaların temel odak noktası olmuştur. Doğrudan yabancı yatırımlar ve büyüme ve beşeri sermaye ve büyüme arasındaki ilişkiyi inceleyen çalışmalar literatürde oldukça yaygındır. Fakat yabancı ortaklık ve beşeri sermaye arasındaki ilişkiyi doğrudan inceleyen çalışmalar, konunun hem ampirik hem de politik önemine rağmen, fazla ele alınmamıştır. Bu çalışmanın temel amacı Türkiye imalat sanayinde yabancı ortaklık ve spesifik beşeri sermaye arasındaki ilişkiyi incelemektir. Dünya Bankası’nın 2019 yılına ait, firma seviyesindeki Dünya İşletme Çalışmaları verisi kullanılmıştır. Birçok firma özelliği, sektör ve bölge değişkenleri ile birlikte, yabancı ortaklığın firmalardaki spesifik beşeri sermaye açısından önem teşkil edip etmediği birçok farklı kesirli yanıt değişkeni regresyon yöntemi tahmin edilerek incelenmiştir. Çalışmanın bulguları şu şekilde özetlenebilir: i) Yabancı ortaklığın firma seviyesinde spesifik beşeri sermaye yoğunluğuna etkisi negatiftir; ii) Bir firmanın daha büyük ya da daha uzun zamandır faaliyette bulunuyor olmasının spesifik beşeri sermaye yoğunluğunu azaltıcı bir etkisi vardır; iii) İhracat yoğunluğu, spesifik beşeri sermaye yoğunluğunu pozitif etkileyen tek firma özelliğidir.
Türkiye imalat sanayi firmalarında özelleşmiş beşeri sermaye yoğunluğu: Yabancı ortaklığın rolü
Keywords: pecific human capital; foreign ownership; Turkey; Spesifik beşeri sermaye; yabancı ortaklık; Türkiye